1994
DOI: 10.1093/geronj/49.5.b224
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Bone Mineral Density From Age-related Decreases in Insulin-like Growth Factor-I and Its Binding Proteins in the Male Rat

Abstract: We evaluated the possibility that age-related decreases in circulating and/or bone-associated insulin-like growth factor-I (IGF-I) and its binding proteins (BPs) were associated with the development of osteopenia in 8-, 16-, and 24-month-old specific pathogen-free Brown Norway/Fischer 344 male rats. We measured bone mineral densities (BMD) of femurs by dual-energy x-ray absorptiometry. IGFs and IGFBPs were extracted from bone and separated by molecular exclusion HPLC before quantitation by specific radioligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Male Fischer 344/Brown Norway rats (6 and 32 mo of age) were purchased from the National Institute on Aging. This strain of rat has increased longevity and decreased cumulative lesion incidence compared with other strains; therefore, aging aspects can be studied in the relative absence of disease (4,38,65). The different ages were chosen to reflect a mature rat (6 mo) and an old rat at ϳ50% mortality (32 mo).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male Fischer 344/Brown Norway rats (6 and 32 mo of age) were purchased from the National Institute on Aging. This strain of rat has increased longevity and decreased cumulative lesion incidence compared with other strains; therefore, aging aspects can be studied in the relative absence of disease (4,38,65). The different ages were chosen to reflect a mature rat (6 mo) and an old rat at ϳ50% mortality (32 mo).…”
Section: Methodsmentioning
confidence: 99%
“…Age-related decreases in serum IGF-I have been described in humans (for review see Ref. 73) and in rats (4), and the circulating levels of IGF-I have been shown to directly regulate bone growth and density (68). Thus we investigated whether IGF-I levels were also sensitive to HS in young and old rats.…”
Section: Hs Reduces the Pool Of Committed Adipocyte Precursors But Nmentioning
confidence: 99%
“…Studies in old rats have shown that the local expression of IGF‐I mRNA in bone declines with age (11) . The content of IGF‐I is lower in old bone as compared with young bone (12) . In addition, the effective dose of IGF‐I required to stimulate DNA synthesis is shifted two orders of magnitude higher for old osteoprogenitor cells (13) .…”
Section: Introductionmentioning
confidence: 99%
“…The use of human bmMSCs in this study was approved by the Institutional Review Board of Miaoli General Hospital. Isolation of bmMSCs from marrow aspirates was performed as described previously 28. Cells were cultured in Dulbecco's modified Eagle's medium (DMEM) (low glucose) (GIBCO-BRL) containing fetal bovine serum (15%) (Hyclone), glutamine, penicillin and streptomycin (GIBCO-BRL), and maintained in a humidified atmosphere containing 5% CO 2 at 37℃.…”
Section: Methodsmentioning
confidence: 99%
“…A causative role that the compromised IGF-1 signaling plays in the aging-related decrease of bmMSCs' osteogenic capability and bone deficit is suggested by several informative findings 26, 27. In experimental animals, it was found that the content of IGF-1 and the local expression of IGF-1 in bone decreased with aging 28-30. It has also been shown that while IGF-1 could consistently activate genes that are related to osteogenic function, the mitogenic activity of IGF-1 was impaired in aged rats 24.…”
Section: Introductionmentioning
confidence: 99%